Does Talk Lead to Action? An Examination of the Relationship between Debate and Funding for NGOs in Canada. (17th July 2019) - Corrigall‐Brown, Catherine; Ho, Mabel
Abstract: All organizations, including nongovernmental organizations (NGOs), need funding to survive and fulfill their mandates. What is the best strategy for securing that funding? Should groups work to attract government attention and be a focus of government debate or should they avoid this type of scrutiny? This article uses innovative data to systematically examine how being the subject of debate in parliament is related to NGO funding for Indigenous, women, and environmental groups. We also examine if the relationship between debate and funding is dependent on the political party in power. We use data collected from Canadian Public Accounts, which lists all grants to groups by the federal government, and the index of Hansard, a full record of parliamentary debates at the federal level in Canada. Our findings demonstrate that the relationship between debate and funding is dependent on the issue area. While debate is positively associated with funding in all areas, it is a stronger predictor of funding for environmental and Indigenous groups than for organizations focusing on women. In addition, the party in power is critical for shaping how debate is related to funding. Debate has a much stronger effect on environmental funding when Liberals are in power than it does when Conservatives control the Prime Minister's office. This research shows that NGOs must be strategic when garnering attention to their cause as more debate does not necessarily lead to more funding across issue areas and contexts. Résumé: Tous les organismes, y compris les ONG, ont besoin de financement pour survivre et bien remplir leur mandat. Quelle est la meilleure stratégie pour obtenir ce financement? Les groupes doivent‐ils rechercher l'attention du gouvernement et susciter des débats gouvernementaux ou doivent‐ils au contraire éviter de se retrouver sous les projecteurs? Cet article a recours à des données novatrices pour examiner systématiquement comment faire l'objet de débats au parlement peut influencer le financement des ONG dans trois domaines : les Autochtones, les femmes et l'environnement. Nous examinons également si la relation entre débat et financement dépend du parti politique au pouvoir. Nous utilisons des données novatrices tirées du comité canadien des comptes publics, qui établit la liste de tous les groupes ayant reçu des subventions de la part du gouvernement fédéral, et Hansard, compte rendu officiel des débats de la Chambre des communes du Canada. Nous avons découvert que le lien entre débats et financement dépend du domaine débattu. Alors que le débat est associé positivement au financement dans tous les domaines, il constitue un meilleur prédicteur de financement des groupes environnementaux et autochtones que de ceux qui visent les femmes. De plus, le parti au pouvoir est critique dans la détermination de la manière dont les débats sont liés au financement. Les débats ont un effet beaucoup plus marquant, dans le cas du financement des groupes environnementaux, lorsque les libéraux sont au pouvoir que lorsque le premier ministre est conservateur. Cette recherche démontre que les ONG doivent faire preuve de stratégie lorsqu'elles cherchent à attirer l'attention sur leur cause, car plus de débats ne conduisent pas nécessairement à un financement plus important pour tous les problèmes et dans tous les contextes.